2009
DOI: 10.4103/0973-3930.50713
|View full text |Cite
|
Sign up to set email alerts
|

Trace and toxic element patterns in nonsmoker patients with noninsulin-dependent diabetes mellitus, impaired glucose tolerance, and fasting glucose

Abstract: PROJECT:Noninsulin dependent diabetes mellitus is supposed to be associated with fluctuations in the plasma levels of several trace elements. There is accumulating evidence that the metabolism of several trace elements is altered in patients with noninsulin dependent diabetes mellitus and that these nutrients might have specific roles in the pathogenesis and progression of this disorder.PROCEDURE:The aim of the present study is to compare the levels of essential trace and toxic elements including lead (Pb), ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 20 publications
7
50
2
1
Order By: Relevance
“…In the present study, the correlation of essential and nonessential elements in scalp hair of DM-2 patients of both genders related to non-diabetic subjects belonging to Pakistan and Ireland was carried out. The results presented in Table 4 for healthy subjects and DM-2 patients confirm higher levels of Cd and Pb while lower values of Mg, Mn, Zn and Cr are associated with diabetes, which are consistent with other studies [31][32][33][34]. The results showed that the level of Mg was significantly lower in scalp hair samples of DM-2 patients as related to referents (P <0.001 ).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, the correlation of essential and nonessential elements in scalp hair of DM-2 patients of both genders related to non-diabetic subjects belonging to Pakistan and Ireland was carried out. The results presented in Table 4 for healthy subjects and DM-2 patients confirm higher levels of Cd and Pb while lower values of Mg, Mn, Zn and Cr are associated with diabetes, which are consistent with other studies [31][32][33][34]. The results showed that the level of Mg was significantly lower in scalp hair samples of DM-2 patients as related to referents (P <0.001 ).…”
Section: Discussionsupporting
confidence: 81%
“…It is a part of many important metalloenzymes like pyruvate carboxylase, arginase, superoxide dismutase and glycosyl-transferase. It plays an essential role for the proper use of choline, thiamine, biotin, vit C and vit E. The Mn as a cofactor of enzymes is also involved in mitochondrial glycoproteins synthesis (Serdar et al, 2009). It is absorbed in small intestine, then bound to albumin in circulation and is transported to liver and excreted in bile.…”
Section: Mnmentioning
confidence: 99%
“…Prevalence of these toxic metals in the environment is potentially alarming and harmful for human health (Schwarzenbach et al, 2010). They are common in the nature and present in air, water and soil, which increases the probability of human exposure (Serdar et al, 2009). Toxic metals react with various proteins in the body that may modify their functions and kinetics.…”
Section: Toxic Metals and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is no evidence of higher levels of mercury in blood of diabetic type 1 or 2. A causal relationship between mercury and pancreatic dysfunction that leads to hyperglycemia and diabetes has been reported, but not all the diabetics have higher levels of this metal [123,124].…”
Section: Metals and Glucose Metabolismmentioning
confidence: 99%